Reconstructing the Gospel : finding freedom from slaveholder religion - Wilson-Hartgrove, Jonathan, 1980-; Barber, William J., II, 1963- (Downers Grove, Illinois : IVP Books, an imprint of InterVarsity Press, 2018)
"'I am a man torn in two. And the gospel I inherited is divided.' Jonathan Wilson-Hartgrove grew up in the Bible Belt in the American South as a faithful church-going Christian. But he gradually came to realize that the gospel his Christianity proclaimed was not good news for everybody. The same Christianity that sang, 'Amazing grace, how sweet the sound' also perpetuated racial injustice and white supremacy in the name of Jesus. His Christianity, he discovered, was the religion of the slaveholder. Just as Reconstruction after the Civil War worked to repair a desperately broken society, our compromised Christianity requires a spiritual reconstruction that undoes the injustices of the past. Wilson-Hartgrove traces his journey from the religion of the slaveholder to the Christianity of Christ. Reconstructing the gospel requires facing the pain of the past and present, from racial blindness to systemic abuses of power. Grappling seriously with troubling history and theology, Wilson-Hartgrove recovers the subversiveness of the gospel that sustained the church through centuries of slavery and oppression, from the civil rights era to the Black Lives Matter movement and beyond. When the gospel is reconstructed, freedom rings both for individuals and for society as a whole. Discover how Jesus continues to save us from ourselves and each other, to repair the breach and heal our land"--
Part I: Slaveholder religion. Christmas on the plantation ; Immoral majority ; Racial blindness ; Living in skin ; This is my body, broken ; A gilded cross in the public square -- Part II: The Christianity of Christ. The other half of history ; Moral revival ; Having church ; Healing the heart -- Epilogue: A letter to my grandfather and my son.
Includes bibliographical references.
Keywords: Racism -- Religious aspects -- Christianity; Liberty -- Religious aspects -- Christianity; Racism -- United States; Race relations -- Religious aspects -- Christianity; United States -- Race relations; Nonfiction